Effects of sex and locality on the abundance of lice on the wild rodent Oligoryzomys nigripes - Fernandes, Fernanda Rodrigues; Cruz, Leonardo Dominici [UNESP]; Linhares, Aricio Xavier (Springer, 2012)
Various factors can affect the parasite distribution on a host. In this study, the influence of sex, body size, and locality of a rodent host, Oligoryzomys nigripes, on lice abundance was investigated. A generalized linear model indicated that the sex and locality of O. nigripes significantly contributed to the variation in lice abundance on the host. The male bias of lice parasitizing the rodent host O. nigripes may be associated with intersexual differences in physiology and behavior, while locality differences in lice abundance may be associated with differences in host density and diversity between the two localities sampled. Studies of host-parasite associations improve the understanding of the ecology of infectious diseases, as well as the evolution of these host-parasite interactions.